2017
DOI: 10.1093/aobpla/plx001
|View full text |Cite
|
Sign up to set email alerts
|

Living on the edge: Conservation genetics of seven thermophilous plant species in a High Arctic archipelago

Abstract: Small and peripheral populations often contain low levels of genetic variation. This may limit their ability to adapt to environmental change, including climate warming. In a recent study published in AoB PLANTS, Birkeland, Skjetne and colleagues show that many rare and threatened plant species in the High Arctic archipelago Svalbard harbour low levels of genetic variation. Most of them are probably relicts from the early Holocene warmer period. They have likely experienced strong genetic founder/bottleneck ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 81 publications
3
23
0
Order By: Relevance
“…A similar conclusion has been recently reached by Birkeland et al. () in a study that identified separate conservation units at the northern distribution boundary of some arctic species. This study demonstrates how the discovery of these refugia can alter our application of conservation efforts, in terms of legal protection, red listing (Abeli, Gentili, Rossi, Bedini, & Foggi, ) and translocation (Birkeland et al., ).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…A similar conclusion has been recently reached by Birkeland et al. () in a study that identified separate conservation units at the northern distribution boundary of some arctic species. This study demonstrates how the discovery of these refugia can alter our application of conservation efforts, in terms of legal protection, red listing (Abeli, Gentili, Rossi, Bedini, & Foggi, ) and translocation (Birkeland et al., ).…”
Section: Introductionsupporting
confidence: 87%
“…() in a study that identified separate conservation units at the northern distribution boundary of some arctic species. This study demonstrates how the discovery of these refugia can alter our application of conservation efforts, in terms of legal protection, red listing (Abeli, Gentili, Rossi, Bedini, & Foggi, ) and translocation (Birkeland et al., ). Finally, identifying marginal population hotspots will enrich our understanding of the causes of endemism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botrychium species show no meaningful genetic differentiation within populations (Farrar, 1998;Hauk and Haufler, 1999) or low genetic differentiation among populations (Camacho and Liston, 2001;Swartz and Brunsfeld, 2002;Birkeland et al, 2017). However, the absence of genetic differentiation reported by previous studies may well stem from low marker resolution.…”
Section: Fine-grained Resolution Of Population Structurementioning
confidence: 92%
“…Previous population genetic studies based on isozymes showed a lack of genetic differentiation among morphologically recognized types (Williams et al, 2016), and the low amount of genetic variation detected within Botrychium populations suggests pervasive self-fertilization (Farrar, 1998;Hauk and Haufler, 1999). Furthermore, genetic differentiation among populations and regions was found to be low suggesting that gene flow may occur (Camacho and Liston, 2001;Swartz and Brunsfeld, 2002;Birkeland et al, 2017). These studies highlight the need for powerful, genome-wide marker systems to resolve population structures, life histories and taxonomy of these early-branching ferns.…”
Section: An Important Genus Lacking Transcriptomic Resources Is Botrymentioning
confidence: 97%